Self-serving bias and tax morale - Kay Blaufus; Matthias Braune; Jochen Hundsdoerfer; Martin Jacob (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
In a real-effort laboratory experiment to manipulate evasion opportunities, we study whether the moral evaluation of tax evasion is subject to a self-serving bias. We find that tax morale is egoistically biased: Subjects with the opportunity to evade taxes judge tax evasion as less unethical as opposed to those who cannot evade. The detection probability does not affect this result. Further, we do not find moral spillover effects, for example, on legal activities.
Keywords: H20; H26; 330; evasion; tax morale; tax compliance; self-serving bias; moral spillover